ANTIPLATELET AND ANTICOAGULANT THERAPY DURING ANGIOPLASTY PROCEDURES FOR ATHEROMATOUS OR FIBROMUSCULAR DYSPLASIA RENAL ARTERY STENOSIS: A SURVEY OF PRACTICES IN EUROPEAN SOCIETY OF HYPERTENSION EXCELLENCE CENTRES (ESH-EC) IN FRANCE. (June 2022) - Bouhanick, Beatrice; Amar, Jacques; Amar, Laurence; Courand, Pierre Yves; Delsart, Pascal; Denolle, Thierry; Doublet, Julien; Fauvel, Jean Pierre; Fesler, Pierre; Girerd, Xavier; Jeune, Sylvain Le; Pelletier, Caroline; et al.
Abstract : Objective: Recommendations framing antiplatelet therapy (APT) and/or anticoagulation (AC) therapy during renal artery angioplasty procedures remain succinct or absent¹. The aim was to describe the practice of using APT and AC in the 17 French ESH-EC during renal artery angioplasties for atheromatous stenoses (AS) or fibromuscular dysplasia stenoses (FMD). Design and method: Sending of a questionnaire via the French Society of Hypertension mailing to collect data with a reminder 1 month later. Results: Are summarized in the table. 12 centres responded partially or completely for AS and 10 for FMD. 2 centres considered that they did not recruit enough; 3 did not respond. Conclusions: In AS, single APT before angioplasty is the rule, while double APT is routine after angioplasty for 1 month, followed by single APT over the long term. In FMD, in most cases (90% of cases) there is no double APT before or after angioplasty (except in the case of dissection), while a single APT is continued in 60% of cases over the long term. Anticoagulants are reserved for bolus injection in operating room (with some exceptions) for both AS and FMD. For AS, the handling of APT (duration, dose) differs, due to the lack of recommendations. In contrast, the use of AC/APT seems to be homogeneous in FMD before and during angioplasty, in accordance with the recommendations ¹. ¹Gornik HL et al. J Hypertens. 2019 Feb;37(2):229-252